Mergers and market power: Evidence from rivals' responses in European markets - Joel Stiebale; Florian Szücs (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2019)
This paper analyzes the effects of mergers and acquisitions on the markups of non-merging rival firms across a broad set of industries. We exploit expert market definitions from the European Commission's merger decisions to identify relevant competitors in narrowly defined product markets. Applying recent methodological advances in the estimation of production functions, we estimate markups as a measure of market power. Our results indicate that rivals significantly increase their markups after mergers relative to a matched control group. Consistent with increases in market power, the effects are particularly pronounced in markets with few players, high initial markups and concentration. We also provide evidence that merger rivals reduce their employment, sales and investment, while their profits increase around the time of a merger.
Keywords: D22; L40; L13; O31; 330; Merger; Markups; Productivity; Market Power; Innovation; Investment